Comparison of Nasoseptal Cartilage Graft Versus Titanium Mesh in Reconstruction of Pure Orbital Blowout Fractures. Issue 4 (28th June 2021) - Mangan, Mehmet Serhat; Goker, Ayse Enise; Yurttaser Ocak, Serap; Uyar, Yavuz
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose: To compare the efficacy of nasoseptal cartilage grafts versus titanium mesh implants in pure orbital blowout fractures. Methods: A retrospective review was performed on 48 patients who had surgical repair of an orbital fracture. Patients who underwent pure orbital blowout fracture repair with either nasoseptal cartilage grafts or titanium mesh implants and at least 1 year postoperative follow-up were included in the study. The clinical features and treatment outcomes were analyzed. Results: Twenty-five patients fulfilled our study criteria and were included in the analyses. Nasoseptal graft was used in 12 patients (48%) while titanium mesh was preferred in 13 patients (52%). Preoperative clinical features including age, size of the floor defect, and preoperative clinical findings (enophthalmos, diplopia, and restriction of ocular motility) were similar between 2 groups. Mean postoperative follow-up was 14.7 ± 2.3 months in the nasoseptal group while it was 16.1 ± 2.5 months in the titanium group ( P  = 0.84). Diplopia and ocular motility limitation were resolved in all patients at the last postoperative follow-up visit, while 1 patient in each group had enophthalmos (8.3% versus 7.6%, P  = 1.0). No patient in the nasoseptal group experienced postoperative complications while 2 patients in the titanium group (15.3%) developed material-related complications ( P  = 0.48). Conclusions: Long-term clinical results of nasoseptal cartilage grafts and titanium mesh implants in pure orbital blowout fractures with preoperative floor defects smaller than 4 cm 2 were comparable. Nasoseptal cartilage grafts may be preferred in patients with septal deviation and no spurs or turbinate hypertrophy.